Chaotic dynamics model based on field-programmable analog array technology - Thair Ali Salih (International Journal of Advances in Applied Sciences, 2022)
Engineering applications in secure communications and encryption based on chaotic signals have attracted a lot of attention in the past decade. This paper presents an extensive study of the chaotic dynamics model of the van der pol oscillator via MATLAB/Simulink simulation and its practical implementation using field-programmable analog matrix techniques. The obtained results show the ease of changing the frequency of the oscillator signal once it is retrieved, creating the required changes, and loading it again according to the required changes. An unlimited number of signals can be generated, allowing them to be used as a chaotic signal oscillator used in many transceiver systems, which require the generation of an unlimited number of such a signal. These research results confirmed that the AN231E04 field-programmable analog array (FPAA) device could be an interesting choice for analog circuit designers, it has the advantage of the ease of use in introducing design changes and testing many critical design solutions.